In-vitro cytotoxicity and apoptosis mechanism of ethyl acetate extract from Trichoderma reesei strain TV221 associated with marine sponge: Stylissa flabelliformis - Erna Prawita Setyowati, Sylvia Utami Tunjung Pratiwi, Purwantiningsih, Indah Purwantini (Journal of Applied Pharmaceutical Science, 2018)
This research aimed to acknowledge the cytotoxic effect of ethyl acetate extract fermented from Trichoderma reesei strain TV221 fungi associated with Stylissa flabelliformis sponge in various cell lines such as WiDr, T41, T47D, Raji, and Vero, as well as to discover the mechanism of cell’s death. The result of fermented fungi T. reesei was extracted with ethyl acetate. Ethyl acetate extract was tested against cell lines using the MTT assay. The result of cytotoxic selectivity test with lowest IC50 price, then apoptosis test with double staining acridine orange-ethidium bromide method was performed Ethyl acetate extract fermented from T. reesei has cytotoxic ability against tumor cell lines (WiDr, T41, T47D, Raji) and is not toxic to normal cell lines (Vero). The test sample can spur apoptosis process on colon cancer cells Widr.
Keywords: Trichoderma reesei strain TV221, cytotoxic effect, apoptosis, Stylissa flabelliformis, associated sponge.